Long Disease Duration Interferes With Therapeutic Effect of Globus Pallidus Internus Pallidal Stimulation in Primary Cervical Dystonia. Issue 3 (1st June 2012) - Yamada, Kazumichi; Hamasaki, Tadashi; Hasegawa, Yu; Kuratsu, Jun‐ichi
<x xml:space="preserve">Abstract</x> Objectives: We retrospectively investigated the correlation between disease duration and the therapeutic effect of globus pallidus internus (GPi) stimulation in patients with primary cervical dystonia (CD). Materials and Methods: Eight patients with CD unresponsive to medical treatments underwent bilateral GPi deep brain stimulation (DBS). They were followed for 63.5 ± 38.2 months (mean ± standard deviation) and were assessed before and at 1, 12, 24, and 36 months after surgery and at their final visit to our outpatient clinic using the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS). Univariate analysis was performed to identify factors that affected their postoperative TWSTRS score. Results: At last follow‐up, disease severity and the degree of disability and pain on the TWSTRS were significantly improved by 70.2%, 76.1%, and 87.1%, respectively (p < 0.05, Wilcoxon signed‐rank test). Neither age nor preoperative CD severity was predictive of postoperative improvement; however, the disease duration affected their reduction rate of TWSTRS severity score at each time point investigated (p < 0.05). Conclusions: Bilateral GPi‐DBS is an effective long‐term therapy in patients with CD. The delivery of GPi stimulation in the earlier course of CD may yield greater postoperative improvement.